2018
DOI: 10.1097/rli.0000000000000420
|View full text |Cite
|
Sign up to set email alerts
|

Photon-Counting CT

Abstract: At matched CT scan protocol settings and identical image reconstruction parameters, the PCD yields superior in-stent lumen delineation of coronary artery stents as compared with conventional EID arrays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 29 publications
3
65
0
1
Order By: Relevance
“…This is mostly because of the smaller pixel size of PCDs compared with that of energy integrating detectors, which are used in typical CT scanners. 2,13 Altogether, these results suggest that SPCCT should have a tumor identification potential beyond current detection. 27 This will have to be tested in an animal model of peritoneal carcinomatosis by simultaneously injecting gadolinium IP to highlight PMs via negative contrast and iodine IV to improve the contrast resolution between normal tissue and PM enhancement.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This is mostly because of the smaller pixel size of PCDs compared with that of energy integrating detectors, which are used in typical CT scanners. 2,13 Altogether, these results suggest that SPCCT should have a tumor identification potential beyond current detection. 27 This will have to be tested in an animal model of peritoneal carcinomatosis by simultaneously injecting gadolinium IP to highlight PMs via negative contrast and iodine IV to improve the contrast resolution between normal tissue and PM enhancement.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, photon-counting detectors (PCDs) allow an exact physical representation of pixel values, with quantitative information processed by the SPCCT system from the spectrum transmitted through the subject. 2 Moreover, PCDs have higher spatial resolution that allows differentiation of smaller structures, such as parenchymal arteries, or very small lesions with a size below the detection limit of standard CT. 2,13…”
mentioning
confidence: 99%
“…However, the measured width of the struts, which was measured approximately 30% more accurately on the SPCCT system than on the other systems, reflects the improved spatial resolution of the SPCCT 7,13,14 . These results are in agreement with the very recent study of Mannil and colleagues, who found a 28.8% increase in intra stent luminal diameter when comparing a photon counting detector (PCD) to a conventional energy integrating detector (EID) 13 . To be noted that in our study, different slice thicknesses were used between the SPCCT and the IQon and B64 system.…”
Section: Discussionmentioning
confidence: 88%
“…Another significant benefit of spectral imaging is the possibility to measure the absolute concentration of contrast agents such as gadolinium, iodine, or gold 13,2022 . Finally, the high spatial resolution of PCDs enables the differentiation of small structures like parenchymal arteries or lesions with sizes below the detection limit of conventional CT 7,23,24 . Accordingly, Mullner et al .…”
Section: Introductionmentioning
confidence: 99%